Contemporary Issues of Legal Certainty, Analogy of law and Legal Interpretation of Law Interrelation - Danielyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2016)
The article refers to the necessity to review the classical characteristics of the constitutional principle of legal certainty. Specifically, it puts forward the viewpoint according to which the pledge for full application of the principle of legal certainty is not merely adoption of legal acts under accurate editing to the extent possible. In the event that editorial accuracy is taken as top priority, the process of making amendments and supplements to the legislation at extremely high frequency takes place, which itself requires suspension of legal norms for a long time thus resulting in disrupt of normal course of regulation of relations. In the present article the following position is substantiated: it is worth reviewing the definitions of terms «analogy» and «interpretation», reinvent their applied values and limits. Particularly, the viewpoint set forth below has been substantiated: as the basis for allowing analogy should serve not legislative branch but the circumstance of improvement or deterioration of the condition of a person in the result of application thereof. Thus, analogy is deemed applicable in those cases when it leads to the improvement of the condition of a person.